2020
DOI: 10.3390/atmos11090905
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MODIS C6.1 and MERRA-2 AOD Using AERONET Observations: A Comparative Study over Turkey

Abstract: This study validated MODIS (Moderate Resolution Imaging Spectroradiometer) of the National Aeronautics and Space Agency, USA, Aqua and Terra Collection 6.1, and MERRA-2 (Modern-ERA Retrospective Analysis for Research and Application) Version 2 of aerosol optical depth (AOD) at 550 nm against AERONET (Aerosol Robotic Network) ground-based sunphotometer observations over Turkey. AERONET AOD data were collected from three sites during the period between 2013 and 2017. Regression analysis showed that overall, seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…3 and 4. Some studies (e.g., Penna et al, 2018;Aldabash et al, 2020) have shown that MODIS and MERRA-2 AODs are consistent in terms of temporal variation; however, MODIS AODs can be higher than MERRA-2 values. The study sectors described in Section 2 were further divided into highly populated (>1 million) and moderately or less populated (<1 million) regions to calculate their mean AODs (Table 1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 and 4. Some studies (e.g., Penna et al, 2018;Aldabash et al, 2020) have shown that MODIS and MERRA-2 AODs are consistent in terms of temporal variation; however, MODIS AODs can be higher than MERRA-2 values. The study sectors described in Section 2 were further divided into highly populated (>1 million) and moderately or less populated (<1 million) regions to calculate their mean AODs (Table 1).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Over the past years, various reanalysis and satellite datasets have provided global aerosol data products, such as the Modern‐Era Retrospective Analysis for Research and Applications, version 2 (MERRA‐2), and the MODerate resolution Imaging Spectroradiometer (MODIS). Numerous studies have used the Aerosol Robotic Network (AERONET) data to evaluate the MERRA‐2 and MODIS AODs over the Middle East region and very good agreement has been reported between AODs from these platforms (Sabetghadam et al ., 2018, 2021; Che et al ., 2019; Aldabash et al ., 2020; Shaheen et al ., 2020; Yousefi et al ., 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier, several authors have reported the assessment of CAMSRA and/or MERRA-2 simulated aerosol optical depth with the AERONET observations. (28)(29)(30)(31) At the same time, limited studies have stated the association of reanalysis data of aerosol mass concentrations with ground-based observations. (32) Previously, Buchard et al (33) reported the comparison of ground-based aerosol mass concentrations measured from approximately 300 sites across the United States with MERRA (version 1) reanalysis data.…”
Section: Introductionmentioning
confidence: 99%